Mutation of BRCA1/2 Gene in Premenopausal Triple-Negative Breast Cancer Patients in West Sumatera - Harahap, Wirsma Arif; Khambri, Daan; Panigoro, Sonar Soni; Hafiz, Muhammad Zaki Abdul (http://dharmais.co.id/, 2025)
Background: The BRCA1/2 mutation rate was found to be higher in triple-negative breast cancer (TNBC) patients depending on young age, and the presence of a family history of breast cancer and ovarian cancer. Research on BRCA1/2 germline mutations that focused on premenopausal TNBC patients in Indonesia has never been carried out. The objective of this research is to determine the BRCA1/2 germline gene mutation status in premenopausal TNBC patients in West Sumatra.Methods: This is a descriptive study conducted at the Surgical Oncology Division of DR. M. Djamil Hospital, Padang from April to July 2023. This study included patients aged 50 years who were diagnosed with the TNBC subtype at Dr. M. Djamil Hospital, Padang from January 2016 to July 2023. Secondary data was collected through the patient’s medical records to observe the TNBC patient’s characteristics. A blood test of TNBC patients was carried out to determine germline mutation of BRCA1/2.Results: 22 patients with TNBC participated in the study. In this study, 4/22 (18.2%) had BRCA2 pathogenic mutations and no BRCA1 pathogenic mutation was found. All patients with BRCA2 pathogenic mutation have the same mutation characteristics, i.e exon 3, genetic variation (c.262_263delCT), amino acids (p.Leu88AlafsTer12), and type of mutation (Frameshift Deletion). Conclusions: TNBC patients in West Sumatra have BRCA2 pathogenic mutations with the same characteristics as the mutations